Mutu Fisik dan Aktivitas Antifungi Sampo Ekstrak Mentimun (Cucumis sativus) terhadap Candida albicans - Jamilatun, Makhabbah; Rusita, Youstiana Dwi; Sari, Esti Perwita (PHARMADEMICA : Jurnal Kefarmasian dan Gizi, 2025)
Dandruff can be caused by microorganisms such as fungi, one of which is Candida albicans. Candida albicans fungus can be inhibited with flavonoids, saponins, and alkaloids. One of the plants that contain this compound is cucumber (Cucumis sativus). Cucumbers are also able to stimulate hair growth and nourish hair loss. This research aims to determine the physical quality to determine quality and antifungal activity of cucumber fruit extract shampoo. The method used in this research was quantitative experimental with four formulas for varying the concentration of active substances from cucumber: F1 (0%), F2 (0.06%), F3 (0.08%), and F4 (0.1%). Cucumber extraction was done using the soxhletation method using 70% ethanol solvent.   The organoleptic test results showed that F0, F1, F2, and F3 had a clear yellow color, a typical herbal odor, thick texture; and homogeneous. The pH of F0, F1, F2, and F3 respectively is 8.52; 8.76; 8.62 and 8.86. The viscosities of F0, F1, F2, and F3 are 1352 mPas, 1441 mPas, 1631 mPas, dan 1690 mPas, respectively. The height of the foam F0, F1, F2, and F3 respectively is 8.3 cm; 8.6cm; 8.6cm; and 8 cm. Antifungal activity has an inhibition zone of F0, F1, F2, and F3 respectively, namely 21.22 mm; 22.47mm; 22.82mm; 24.35mm. The results obtained show that the cucumber extract shampoo meets the physical qualities and has very strong antifungal activity.